Dari Tradisi Lisan ke Teks Tertulis: Gagasan Neuwirth Tentang Aspek Oralitas al-Qur'ān - Agustono, Ihwan; Ali Mahfuz Munawar (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
Recent Qur’ānic scholarship has increasingly revisited the relationship between the oral and written dimensions of revelation. This article examines these dimensions through Angelika Neuwirth’s concept of pre-canonical reading, focusing on Sūrah Al-Ikhlāṣ. Neuwirth approaches the Qur’ān from literary, historical, and comparative perspectives, emphasizing that its oral features—such as rhythm, recitation, and audience interaction—are vital for understanding how the Qur’ān initially communicated its message. She argues that the process of codification transformed these living oral expressions into a fixed text, often separating the Qur’ān from its dynamic historical setting. By re-examining Sūrah Al-Ikhlāṣ within its early socio-historical context, this study shows that its concise monotheistic message still carries traces of orality through its sound patterns, rhetorical balance, and dialogical tone. The analysis highlights Neuwirth’s contribution to Qur’ānic studies by bridging orality and textuality, showing the Qur’ān as both a spoken revelation and a historical document shaped through stages of transmission and canonization.